Hydrogen bonds in polymer blends - He, Yong; Zhu, Bo; Inoue, Yoshio (Progress in polymer science, 2004)
The hydrogen bond in polymer blends is an interesting and important subject of research as its presence usually enhances the miscibility of the blend. Here, the factors affecting the formation and stability of hydrogen bonds, the effects of hydrogen bonds on the miscibility and the properties of blends, and methods to incorporate inter-associated hydrogen bonds into immiscible blends are reviewed, based on work over the last twenty or so years.